2016
DOI: 10.1073/pnas.1616168113
|View full text |Cite
|
Sign up to set email alerts
|

VEGF-B gene therapy inhibits doxorubicin-induced cardiotoxicity by endothelial protection

Abstract: Congestive heart failure is one of the leading causes of disability in long-term survivors of cancer. The anthracycline antibiotic doxorubicin (DOX) is used to treat a variety of cancers, but its utility is limited by its cumulative cardiotoxicity. As advances in cancer treatment have decreased cancer mortality, DOX-induced cardiomyopathy has become an increasing problem. However, the current means to alleviate the cardiotoxicity of DOX are limited. We considered that vascular endothelial growth factor-B (VEGF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
89
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 39 publications
8
89
0
Order By: Relevance
“…This result is not inconsistent with recent work by the Alitalo group showing that therapeutic over-expression of VEGFB (which like PlGF binds only VEGFR1) in mice improves metabolic health even following endothelial Flt1 gene deletion, and inhibits doxorubicin-induced cardiotoxicity [54, 87]. Competition between ligands is concentration-dependent, and in these studies, VEGFB protein levels were elevated 20-fold or more in serum, heart, liver, and white adipose tissue.…”
Section: Discussionsupporting
(Expert classified)
“…This result is not inconsistent with recent work by the Alitalo group showing that therapeutic over-expression of VEGFB (which like PlGF binds only VEGFR1) in mice improves metabolic health even following endothelial Flt1 gene deletion, and inhibits doxorubicin-induced cardiotoxicity [54, 87]. Competition between ligands is concentration-dependent, and in these studies, VEGFB protein levels were elevated 20-fold or more in serum, heart, liver, and white adipose tissue.…”
Section: Discussionsupporting
(Expert classified)
“…Our data are in accordance with a previous study demonstrating that VO-PTEN inhibition promoted cell survival and decreased apoptosis postmyocardial infarction (16). Recently, a study by Rasanen et al (33) showed that VEGF-B inhibits DIC and prevents apoptotic cell death in endothelial cells; therefore, it would be interesting to analyze whether the PTEN inhibitor VO also inhibits endothelial cell apoptosis, in addition to the VSMCs and cardiomyocytes in the present study. Moreover, our data suggest that inhibition of PTEN by VO promotes myocardial cell survival after Doxo cardiotoxic assault through upregulation of the AKT pathway, which has been demonstrated in other adverse cardiac conditions (20,37).…”
Section: Discussionsupporting
confidence: 93%
“…The cumulative cardiotoxicity induced by DOX is associated with the development of chronic systolic and irreversible heart failure, which is related to the dosage and duration of treatment . Thus, the prevention of cardiac atrophy and dysfunction could improve the efficacy of cancer chemotherapy and enhance the chances of patient survival . Standard heart failure treatment should generally be initiated with the earliest detection of cardiotoxicity by a combination of biomarkers and imaging studies .…”
Section: Discussionmentioning
confidence: 99%